Proceedings of the 2014 Indian Conference on Computer Vision Graphics and Image Processing 2014
DOI: 10.1145/2683483.2683516
|View full text |Cite
|
Sign up to set email alerts
|

Compression of Noisy Depth Image using Planes

Abstract: This paper investigates compression of depth images -particularly, noisy depth images -captured by depth sensors like Kinect. Our scheme is based on incrementally detecting planes in depth images and then storing the plane parameters instead of the depth information of the pixels lying on the detected planes. Residuals are then computed and compressed using standard image compression techniques. Our technique incorporates the input error model for comprehensive and accurate plane detection. Thereby, this accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…One of the advantages of this method is its applications in different types of holograms [43]. Modi et al suggested a compression method based on 3D image estimation by collecting 2D planes and then storing the plane parameters instead of depth information [44]. In another research, several target holograms were encoded into pairs of front and rear phase distorting surfaces [45].…”
Section: Other Methodsmentioning
confidence: 99%
“…One of the advantages of this method is its applications in different types of holograms [43]. Modi et al suggested a compression method based on 3D image estimation by collecting 2D planes and then storing the plane parameters instead of depth information [44]. In another research, several target holograms were encoded into pairs of front and rear phase distorting surfaces [45].…”
Section: Other Methodsmentioning
confidence: 99%